(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The article focuses on the organization of grain clusters in Uzbekistan, as well as the organizational and theoretical aspects of the role of this system in the agriculture of our country, where there are some problems that the author proposes to solve through cluster networks and the socio-economic situation.